2020
DOI: 10.1111/hiv.13029
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone use and shorter electrocardiographic QT interval duration in men living with and without HIV

Abstract: Objectives Testosterone usage (T‐use) may alter risk factors for sudden cardiac death in men living with HIV (MLWH). Electrocardiographic QT interval prolongation, which could potentiate ventricular arrhythmias, has previously been associated with HIV infection and, separately, with low testosterone levels. We investigated whether T‐use shortens the QT interval duration in MLWH and HIV‐uninfected men. Methods We utilized data from the Multicenter AIDS Cohort Study, a prospective, longitudinal study of HIV infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In men, testosterone ranges from 9-38 nmol/L and has QT shortening effects in a dose dependent manner, which become evident as testosterone rises with puberty (1). In different patient populations high testosterone levels (exogenous and endogenous) resulted in significant QT interval shortening in both men and women (8)(9)(10). For instance,Schwartz et al (8), showed that older men and women exposed to testosterone for 12 weeks presented with significant QT interval shortening (for men: 385 ± 28ms to 382 ± 28ms, p < 0.002; and for women: 400 ± 25ms to 397 ± 23ms, p = 0.06), when compared to placebo.…”
Section: Effects Of Testosterone On the Qt Interval Of Humansmentioning
confidence: 99%
“…In men, testosterone ranges from 9-38 nmol/L and has QT shortening effects in a dose dependent manner, which become evident as testosterone rises with puberty (1). In different patient populations high testosterone levels (exogenous and endogenous) resulted in significant QT interval shortening in both men and women (8)(9)(10). For instance,Schwartz et al (8), showed that older men and women exposed to testosterone for 12 weeks presented with significant QT interval shortening (for men: 385 ± 28ms to 382 ± 28ms, p < 0.002; and for women: 400 ± 25ms to 397 ± 23ms, p = 0.06), when compared to placebo.…”
Section: Effects Of Testosterone On the Qt Interval Of Humansmentioning
confidence: 99%